ANALISIS IMPLEMENTASI PEMBELAJARAN BERDIFERENSIASI PROSES PEMBELAJARAN DI MADRASAH IBTIDAIYAH BERDASARKAN KONDISI SISWA DAN GURU - Weni Tria Anugrah Putri (Jurnal Muassis Pendidikan Dasar, 2026)
The implementation of differentiated instruction in the learning process at Islamic primary schools (Madrasah Ibtidaiyah) has become an issue that deserves particular attention. This study aims to describe the results of an analysis of the implementation of differentiated instruction in the learning process at Madrasah Ibtidaiyah based on student learning outcome standards. The study employed a qualitative approach using the Systematic Literature Review (SLR) method. The analysis was grounded in Arthur Combs’ humanistic theory. Research data were collected through documentation techniques, and the research instrument consisted of 10 scientific articles focusing on differentiated instruction in Madrasah Ibtidaiyah. To facilitate the identification of relevant articles, the researchers used the Publish or Perish application with Google Scholar as the data source. The findings indicate that differentiated instruction has been widely implemented and promoted by various stakeholders. However, a crucial aspect of this approach is often overlooked, namely response. This refers to the reciprocal expectations between teachers and students, specifically responses that align with students’ individual conditions and characteristics. An important issue for further discussion is the type of responses teachers receive from students when various instructional innovations are introduced. The more positive and appropriate the students’ responses are, the easier it becomes to implement differentiated instruction effectively.